STUDI KOMPARATIF : TEORI EDWARD LEE THORNDIKE DAN IMAM AL GHAZALI DALAM IMPLEMENTASINYA DI PEMBELAJARAN ANAK USIA DINI - Nur Kolis; Aisyah Fajar Putri Artini (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
Learning is not just a process of transferring knowledge (transfer of knowledge), but also a transformation or transformation; be it knowledge, skills, and values. There are several learning theories that have been coined by figures from both the West and Islam to realize effective learning. Edward Lee Thorndike's learning theory emphasizes more on learning events that can be accepted by reason and can be proven through the five senses (rational-empirical). While the learning theory promoted by Al Ghazali not only pays attention to rational-empirical learning events, but also pays attention to normative-qualitative ones. The trial and error learning process is carried out by providing a stimulus to get a response that is expected to be used to provide motivation for early childhood learning. In addition, so that it is not just mechanistic considering that children are not robots that do not have feelings, children must also be equipped with religious values ??that can provide motivation from within the child itself. Because the task of educators is to help children develop all the potential they have until they reach maturity, which will be formulated by educators, both methods and materials must refer to children, namely on aspects of their development which are always based on moral formation.